Intrigues facing Competence-Based Approach in Teaching Chemistry among East African states. A Comparative Study - Ochieng , O Anthony; Agunda, Josephine (Journal of Education and Practice, 2025)
Purpose: The implementation of the Competence-Based Approach (CBA) in teaching chemistry across East African states has been intricately interwoven with context-specific challenges, and this study therefore sought to examine both the obstacles and opportunities shaping CBA practice, with the overarching aim of enhancing learners’ scientific inquiry, problem-solving abilities, and meaningful application of chemical concepts. Methodology: Using a comparative design, data were collected from Kenya, Uganda, Tanzania, Rwanda, and Burundi through questionnaires, classroom observations, and rubric-based evaluations. Instrument reliability was rigorously assessed, with Cronbach’s alpha values ranging from 0.75 to 0.85 across the five major subscales of CBA implementation which includes pedagogical competence, learner engagement, practical chemistry activities, learner participation and use of improvised materials, thus confirming the robustness of the tools in capturing CBA-aligned instruction. Findings: Findings indicate that inadequate laboratory infrastructure, overcrowded classrooms, limited access to teaching materials, and insufficient teacher preparedness significantly constrain effective CBA delivery. Socioeconomic disparities, linguistic diversity, and inconsistent curriculum alignment further impede the translation of competency frameworks into authentic learning experiences. Nonetheless, the study shows that CBA can be adapted to local realities through low-cost experiments, contextualized tasks, and sustained professional development for teachers. Unique Contribution to Theory, Practice and Policy: This study contributes to theory, practice, and policy by highlighting context-responsive strategies for implementing CBA in resource-constrained settings, providing evidence for targeted interventions, and informing curriculum and policy design to bridge the gap between aspirations and classroom realities.